The Role of Baznas’ Zakat Community Development (ZCD) in Efforts to Improve the Welfare of the Lubuk Bangkar Village Community, Jambi - Kurniawan , Bambang; Habibah, G.W.I. Awal; Handayani, Sulis (ILTIZAM Journal of Shariah Economics Research, 2023)
This research aims to (1) Find out the role of ZCD in improving the welfare of the people of Lubuk Bangkar Village and the Islamic economic perspective for the role of ZCD (2) What are the factors that inhibit and encourage the ZCD program in improving the welfare of the people of Lubuk Bangkar Village (3) What is the welfare condition of the people of Lubuk Bangkar Village after the ZCD program. This research method uses descriptive qualitative with primary and secondary data types and data collection uses observation, documentation and interview techniques. The research results show (1) Improving community welfare, empowering the community’s economy, providing capital and facilities, providing assistance and coaching. The ZCD program in Lubuk Bangkar Village has fulfilled the principles of the ZCD program, namely, trustworthy and responsible, sustainable, participatory and integrated. And plays a role in various aspects, namely economic aspects, da’wah, education and health. (2) Unavailability of distributors to buy the community’s products or harvests, inaccurate selection of program types and inadequate facilities as well as late arrival of feed to livestock and fisheries communities. Meanwhile, the driving factor is: because Lubuk Bangkar Village is a village with underdeveloped areas and the average population is underprivileged, Baznas RI wants to develop human resources or natural resources in Lubuk Bangkar Village. (3) The percentage of poor people became 58.31% of the total population of 1,197 people and the number of unemployed people became 183 people. As well as increasing the level of public health, improving the quality of public education, creating jobs and providing employment opportunities for the community (mustahik), reducing poverty and unemployment rates. And the facilities that have been provided by BAZNAS are very helpful for the sustainability and welfare of the community in Lubuk Bangkar Village so that it is easier for the community to achieve a prosperous life and to be better at developing their own potential.